Links from Genome Proteins to Known 3-D Structures - Wang, Yanli; Bryant, Stephen; Tatusov, Roman; Tatusova, Tatiana

(untitled) (Genome Research, 2000)
We describe a genome annotation service provided by the Entrez browser, http://www.ncbi.nlm.nih.gov/entrez. All protein products identified in fully sequenced microbial genomes have been compared with proteins with known 3-D structure by use of the BLAST sequence comparison algorithm. For the ∼20% of genome proteins in which unambiguous sequence similarity is detected, Entrez provides a link from the gene product to its predicted structure. The service uses the Cn3D molecular graphics viewer to present a 3-D view of the known structure, together with an alignment display mapping conserved residues from the genome protein onto the known structure. Using an example from Aeropyrum pernix, we illustrate how mapping to a 3-D structure can confirm predictions of biological function.